Analisis Industri Perbankan Tahun 2007-2016 dengan Pendekatan SCP: Studi Kasus Negara Indonesia dan Filipina - Handayani Novika Sari; Moh. Adenan; Agus Luthfi (UPT Penerbitan Universitas Jember, 2019)
The phenomenon of the global financial crisis in 2008 has an impact on the instability of banks, so the banking industry is changes. The emerging change of the banking industry, as a result of the bank's efforts to increase profitability. The structure- conduct-performance analysis becomes an appropriate paradigm for analyzing changes in the banking industry using three minds: traditional hypotheses, differentiation hypotheses, and efficiency hypotheses. The purpose of this study was to determine the effect of market structure and behavior variables on banking profitability. The method used in this study was the calculation of the ratio of concentration, HHI, and fixed effect model in the banking industry of Indonesian and the Philippines. The results of this study indicated that the market structure of the Indonesian banking industry was in a strict oligopoly condition so that it undergoes a change towards increasingly concentrated competition and into the traditional hypotheses, where the concentration ratio (CR4) could affect the ROA. In addition, NIM and CAR had a significantly positive effect, but LDR and NPL had no significantly negative effect on profitability. Other findings indicated that market structure of the Philippine banking industry was in a loose oligopoly condition affecting to experience efficiently competition and categoried into the efficiently hypotheses, where market share (MS) could affect ROA. In addition, NIM had no significantly positive effect, CAR had significantly positive effect, NPL and negative LDR had no significant effect on profitability. Keywords: Efficiency Hypothesis, Traditional Hypothesis, Profitability, Market Structure.